Lessons from Central America: Action Research in an Adult English as a Foreign Language Program - Robert E. Nolan (Adult Education Research Conference, 2000)
Analysts of policy have hitherto not paid much attention to how policy language acts to build up representations of reality. This paper agues for the usefulness of a discursive approach to policy analysis, and illustrates it in the context of emerging policies for ‘lifelong learning’.